IMPULSIVE BUYING IN CIREBON TEENAGERS TRIGGERED BY EMOTIONAL COPING BEHAVIOR - Raden Putri Zalfaa Faadhilah Taqiy , Shopa Shopiatul Fitria , Widya Septiani , Devita Aqilla , Farida Nurfalah , Dedet Erawati (Chelonian Research Foundation, 2024)
This research is motivated by the increasingly advanced e-commerce in today's digital world, becoming the main influence on teenagers' shopping patterns which causes the growth of more dominant consumer behavior. So that today's teenagers do not tend to prioritize secondary needs in their daily lives. The aim of this research is to analyze how much influence teenagers' emotional behavior has on impulsive purchases which cannot be separated from the spotlight on lifestyle and existence. The research was used using quantitative research methods, the Slovin formula and alternative data collection using a questionnaire with a total of 100 respondents (41 male respondents and 59 female respondents). The results prove that price discounts in e-commerce have a positive effect on impulse buying among teenagers in Cirebon. From the final observation results, it can be seen that the data collected shows that the number of online impulsive purchases among teenagers in Cirebon is very high, this can be seen from the answers to the attached questionnaire. The results of the data show that teenagers who make the most impulsive purchases are women for the reason of shopping because there are flash sales at certain events. Keywords: Impulsive; Shopping; Lifestyle; E-Commerce